Viral Hemorrhagic Fevers – A Recurrent Public Health Threat - Shannon Alyassiry, Manar Radhi (American Journal of Biology and Natural Sciences, 2025)
Viral Hemorrhagic Fever (VHFs) encompasses a wide array of systemic diseases The viral pathogens associated with VHF reveal considerable taxonomic diversity; but they are similar by their genomic makeup, where all being enveloped, and have a single-strand RNA. Routes of transmission to humans include handling infected animals reservoirs or via arthropod vectors. Despite their limited geographic distributions, these viruses considered continual natural infectious impendences. As revealed in most recent classifications by International Committee on Taxonomy of Virus, main VHF-occasion agents are classified to seven distinct families including: Hantaviridae, Nairoviridae, Phenuiviridae, Filoviridae, Paramyxoviridae, Arenaviridae, and Flaviviridae. These viruses have common core biological features, such as containing an enveloped single-strand RNA genome, target primarydendritic / monocyte/ macrophage cells, undergo cytoplasmic replication, and produce gastrointestinal and neurological symptoms. Severe cases are interlinked with high viremia levels in the blood. These viral entities pose significant threats to public health with their alarmingly high rates of morbidity and mortality This overview seeks to illuminate the intricacies of viral hemorrhagic fevers: examining their causes, symptoms, modes of transmission, prevention strategies, and the treatments that exist. It’s a call to action—raising awareness about the grave dangers posed by VHFs and fortifying efforts to halt their spread. The reality is stark: hemorrhagic fever is a formidable foe for humanity, boasting a high mortality rate thanks to its virulent nature.